PERAN AKTOR NON-NEGARA DALAM CITIZEN DIPLOMACY PADA AUSTRALIA-INDONESIA YOUTH EXCHANGE PROGRAM (AIYEP) 2020-2022 - Nurshabrina, Hanifah (Global and Policy Journal of International Relations, 2024)
Citizen diplomacy is a medium for establishing people to people contact which is carried out through cultural understanding. One of the diplomatic activities carried out by Australia and Indonesia is through holding AIYEP. The AIYEP program is held every year with the aim of bridging interactions between the two countries in an effort to maintain the stability of bilateral relations between Australia and Indonesia. An example of the AIYEP program is a cultural exhibition held by the two countries under the auspices of the Ministry of Youth and Sports (KEMENPORA) and the Australian Government Department of Foreign Affairs and Trade (DFAT). In the AIYEP program, young people are given the opportunity to contribute to opening up space for interaction through cultural products from the two countries, facilitating communication that produces quality emotional relationships and facilitating the realization of friendly relations between the two countries. The benchmark for the success of the program is increasing people to people contact through cultural interactions expressed in art performances, resolution of global issues even in the Covid-19 pandemic situation. Therefore, this research seeks to examine the role of non-state actors in Icitizen diplomacy in 2021-2022.Keywords: Youth, Citizen Diplomacy, Indonesia, AustraliaCitizen diplomacy menjadi media dalam pembentukan people to people contact yang dilakukan melalui cultural understanding. Salah satu kegiatan diplomasi yang dilakukan oleh Australia dan Indonesia yaitu melalui penyelenggaraan AIYEP. Program AIYEP diadakan setiap tahun bertujuan untuk menjembatani interaksi kedua negara dalam upaya menjaga stabilitas hubungan bilateral Australia dan Indonesia. Contoh dari program AIYEP yaitu pameran budaya yang diadakan kedua negara di bawah naungan Kementerian Pemuda dan Olahraga (KEMENPORA) dan Australia Government Department of Foreign Affairs and TradeI (DFAT). Pada program AIYEP para pemuda diberikan kesempatan untuk berkontribusi dalam membuka ruang interaksi melalui produk budaya kedua negara, memfasilitasi komunikasi yang menghasilkan hubungan emosional yang berkualitas dan memfasilitasi untuk menjalin hubungan persahabatan antar kedua negara. Tolak ukur dalam keberhasilan program yaitu meningkatnya people to people contact melalui interaksi budaya yang dituangkan dalam pertunjukan seni, penyelsaian isu global dan sebagainya, walaupun dalam situasi pandemi Covid-19. Sehingga, pada penelitian ini berusaha untuk mengkaji peran aktor non-negara dalam citizen diplomacy di tahun 2021-2022.Kata Kunci: Pemuda, Citizen Diplomacy, Indonesia, AustraliaDOI: https://doi.org/10.33005/jgp.v12i01.4316